Which anthropometric and metabolic index is superior in hypertension prediction among overweight/obese adults? - Abolhasani M; Maghbouli N; Karbalai Saleh S; Aghsaeifar Z; Sazgara F; Tahmasebi M; Ashraf H; Haidar Ali J (Dove Medical Press, 2021)
Maryam Abolhasani,1,* Nastaran Maghbouli,2,* Shahrokh Karbalai Saleh,3 Ziba Aghsaeifar,4 Faeze Sazgara,5 Maryam Tahmasebi,6 Haleh Ashraf,7 Jemal Haidar Ali8,* 1Cardiac Primary Prevention Research Center (CPPRC), Tehran Heart Center, Tehran University of Medical Sciences, Tehran, Iran; 2Physical Medicine and Rehabilitation Department, Tehran University of Medical Sciences, Tehran, Iran; 3Department of Cardiology, Sina Hospital, Tehran University of Medical Sciences, Tehran, Iran; 4Department of Internal Medicine, Sina Hospital, Tehran University of Medical Sciences, Tehran, Iran; 5Department of Radiology, Guilan University of Medical Sciences, Rasht, Guilan, Iran; 6Department of Cardiology, Amir Al Momenin Hospital, Islamic Azad University of Medical Sciences, Tehran, Iran; 7Cardiac Primary Prevention Research Center (CPPRC), Tehran Heart Center and Research Development Center, Sina Hospital, Tehran University of Medical Sciences, Tehran, Iran; 8Department of Public Health Nutrition, School of Public Health, College of Health Sciences, Addis Ababa University, Addis Ababa, Ethiopia*These authors contributed equally to this workCorrespondence: Jemal Haidar AliAddis Ababa University, College of Health Sciences, School of Public Health, Department of Public Health Nutrition, P.O. Box: 27285, Addis Ababa, 1000, EthiopiaTel +251 115547465; +251 911505465Email hjemal@gmail.comHaleh AshrafResearch Development Center, Sina Hospital, Emam Khomeini St., Tehran, 1136746911, IranFax +98 21-66348553Email hashraf@sina.tums.ac.irBackground: Although the effectiveness of some combined anthropometric and metabolic scores were evaluated in hypertension prediction, none of them had addressed their accuracy in association with overweight/obese populations. This study examined the accuracy of several anthropometric parameters in this regard and compared the novel indices to the ancient ones.Methods: Through a cross-sectional study, 5115 patients have been evaluated at the weight loss clinic. Data on demographic information, anthropometric indices, and biochemical measurements were assembled into a checklist. Multivariable regression modeling and the area under the receiver-operating characteristic (ROC) were analyzed using SPSS version 20. To find new combined scores, SEM (structural equation modeling) analysis was also adopted. P-values < 0.05 were considered statistically significant.Results: Considering ancient indices, WHtR (waist-to-height ratio) showed a sufficient area under the curve in predicting hypertension among both genders concomitant with WC (waist circumference) in men, and BRI (body roundness index) in women as highest AUC. The highest odds ratio (OR) for the presence of hypertension, based on the age-adjusted model, was BRI in females (OR, 3.335; 95% confidence interval [CI], 1.58- 7.28) and WC in males (OR, 13.478; 95% CI: 1.99- 45.02). The combined scores were not superior to the single ones.Conclusion: The most powerful association between hypertension and sufficient discrimination ability of normotensives from hypertensive patients was detected for BRI in women and WC among men. However, neither the BSI and BAI nor FMI and FFMI showed superiority to WC or WHtR in predicting the presence of hypertension.Keywords: prediction, hypertension, obesity, anthropometric indices, novel indices, Iran